2019
DOI: 10.1101/668756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A TetR-family protein activates transcription from a new promoter motif associated with essential genes for autotrophic growth in acetogens

Abstract: Acetogens can fix carbon (CO or CO2) into acetyl-CoA via the Wood-Ljungdahl pathway (WLP) that also makes them attractive cell factories for the production of fuels and chemicals from waste feedstocks. Although most biochemical details of the WLP are well understood and systems-level characterisation of acetogen metabolism has recently improved, key transcriptional features such as promoter motifs and transcriptional regulators are still unknown in acetogens. Here, we use differential RNA-sequencing to identif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…One recent study investigating the transcriptome of Clostridioides difficile strain 630 identified the RBS to be aGGAGg for the majority of genes for which transcripts could be detected (64) suggesting high conservation of this sequence per se in this species. A similar finding was made for Clostridium autoethanogenum (65). Prior to the development of omic tools, studies focusing on individual genes have also reported AGGAGG as the likely RBS for other species of Clostridium including the type E toxin gene of C. botulinum (66), colA encoding collagenase of C. perfringens (67), celA gene encoding endoglucanase A of C. themocellum (68) to name but a few.…”
Section: Discussionmentioning
confidence: 52%
“…One recent study investigating the transcriptome of Clostridioides difficile strain 630 identified the RBS to be aGGAGg for the majority of genes for which transcripts could be detected (64) suggesting high conservation of this sequence per se in this species. A similar finding was made for Clostridium autoethanogenum (65). Prior to the development of omic tools, studies focusing on individual genes have also reported AGGAGG as the likely RBS for other species of Clostridium including the type E toxin gene of C. botulinum (66), colA encoding collagenase of C. perfringens (67), celA gene encoding endoglucanase A of C. themocellum (68) to name but a few.…”
Section: Discussionmentioning
confidence: 52%